HEROISM OF ROBERT NEVILLE IN I AM LEGEND MOVIE - SAPTONO, WILLIAM NICO (LANTERN (Journal on English Language, Culture and Literature), 2015)
I am Legend is a film that tells about a military scientist who struggles to save human extinction from zombie virus. The purpose of this paper is to show the nature of heroism which exist in the protagonist’s characters. The writer uses library research in collecting the data. This analysis is supported by intrinsic elements as cinematography. In analyzing the extrinsic elements, the author uses the theory of heroism. The result of this paper is that Neville shows heroism act such as being decisive, creative in finding solution, being a religious man, helping and fighting the enemy. Those are aspects which represent characteristics of heroism in Neville.